Expression profiling and transcriptional regulation of the SRS transcription factor gene family of common bean (Phaseolus vulgaris) in symbiosis with Rhizobium etli - Litzy Ayra; Gladys Jiménez-Nopala; Gabriela Guerrero; Sara Isabel Fuentes; Alfonso Leija; Mario Ramírez; Georgina Hernández (PLoS ONE, 2025)
The SRS/STY transcription factors from the model legumes: Lotus japonicus and Medicago truncatula, are part of regulatory networks that play relevant roles for nodule development during the N-fixing symbiosis with rhizobia. In this work we analyzed the participation of the PvSRS transcription factors from common bean (Phaseolus vulgaris), a most important legume crop, in the symbiosis with Rhizobium etli. Our phylogenetic analysis of SRS TFs across five plant species, including four legumes and Arabidopsis thaliana, identified clades that group SRS proteins that are highly expressed in legume nodules and in Arabidopsis roots. A qRT-PCR expression analysis of the 10 PvSRS in root/nodule of inoculated plants, revealed that all the PvSRS genes are expressed at different stages of the symbiosis, albeit at different levels. Based on what is known for L. japonicus, we demonstrated that the PvSRS10 gene -with highest expression during symbiosis- is transcriptionally activated by NF-Y transcription factor, thus indicating its participation in the NIN-NF-Y regulatory cascade. Based on our previous work about the relevant role of members from the MADS-domain/AGL transcription factors as regulators of the N-fixing symbiosis, in this work we demonstrated the transcriptional regulation of PvSRS10 by the MADS-TF PvFUL-like. Analysis of protein-protein interaction networks predicted thatPvSRS5 and PvSRS6 interact with proteins involved in transcriptional regulation and the auxin-activated signaling pathway. The regulatory mechanisms of PvSRS TF in common bean symbiosis may be related to auxin biosynthesis regulation, that is essential for determinate nodules development. Our study highlights the role of PvSRS TF in the N-/fixing symbiosis, a relevant process for sustainable agriculture.